Physical Characteristic and Organoleptic of Egg Tofu with Different Types of Egg for Optimal Protein Requirements (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2026)
Egg tofu is one of the foods that contains high protein because it is made from a mixture of soybeansand eggs. Eggs have complete nutritional content ranging from protein, fat, vitamins and minerals. Thisstudy aims to analyze the physical and organoleptic properties of egg tofu with the addition of varioustypes of eggs, namely chicken eggs, free-range chicken eggs, duck eggs and IPB D1 chicken eggs. Theanalysis carried out included pH, water holding capacity (WHC), water absorption index (WAI), watersolubility index (WSI), and Texture with an ANOVA test followed by Tukey and Duncan’s further test,and Organoleptic data were analyzed using the Kruskal–Wallis test. The results of the analysis showedthat only the WHC value was significantly different (P